The effect of tack number and balloon trocar use on acute post-operative pain scores of patients who underwent TEP repair of inguinal hernia - Karaca, Fatih Can; Atasoy, Deniz (Journal of Surgery and Medicine, 2020)
Aim: As the novel technology on surgical procedures evolve, the management and amelioration strategies for postoperative pain gains importance for surgeons to improve patients’ life quality and postoperative outcomes. In this study, we aimed to compare the number of tacks placed during surgery and the use of intra-operative balloon trocars during TEP repair of inguinal hernias with respect to post-operative early pain scores. Methods: A total of 83 patients were included in this prospective cohort study, 59 being in the 0-1 tack group and 24 in the 2 tacks group. Balloon trocar was used in 32 patients. All patients underwent laparoscopic TEP inguinal hernia repair. Groups were compared with respect to pain scores on 3rd, 12th and 24th postoperative hours. Results: Pain score was better in no balloon trocar+2 tacks group when compared to balloon trocar+2 tacks and no balloon trocar+0-1 tack group at the 24th postoperative hour (P=0.02 and P=0.007, respectively), and in the balloon trocar+0-1 tack group than that of the no balloon trocar+0-1 tack group (P=0.004). There was no statistically significant difference between these four groups in terms of pain score on the 3rd and 12th hours of surgery (P=0.46 and P=0.24, respectively). Patients in the 0-1 tack group reported less pain on the 24th postoperative hour (3.1 (6.3) vs 14.1 (21.8); P=0.32). Conclusion: Using less number of tacks and avoiding using balloon trocar result in lower pain scores following laparoscopic TEP repair of inguinal hernias.